Characterization of municipal solid waste as potential fuel for energy needs - Uler-Zefikj, Monika, Godyń, Katarzyna, Tokarczyk, Katarzyna, & Filkoski, Risto V. (MDPI, 2025)
The continued expansion of cities in economic, population and geographical terms leads to significant environmental and infrastructural pressures, including the need for efficient municipal solid waste (MSW) management. This research focuses on the characterization of MSW generated in the city of Skopje and the investigation of its thermo-physical properties and energy utilization potential. The analyses cover physical and chemical properties, including density, moisture content, volatile matter, ash, and higher heating value, using adequate testing methods. The results indicate that MSW has a relatively high gross calorific value, surpassing typical MSW ranges comparable to those of solid fossil fuels. With approximately 79.42% volatile matter and a low ash content of 7.76%, the considered MSW demonstrates excellent combustibility. Chemical analysis reveals high carbon (53.12%) and hydrogen (7.69%) levels, supporting high energy value, while low nitrogen (0.84%) and sulfur (0.26%) levels ensure minimal NOx and SOx emissions. These characteristics position MSW as a suitable feedstock for energy production in incineration facilities. However, the heterogeneous composition of MSW presents challenges to process stability, necessitating prior waste preparation. The research concludes that harnessing waste energy potential could contribute to sustainability, reduce reliance on fossil fuels, and improve the environmental conditions in large urban areas.
Keywords: calorific value; incineration; MSW; proximate analysis; solid waste; ultimate analysis